One-Step Synthesized Pt-on-NiCo Nanostructures for Oxygen Reduction with High Activity and Long-Term Stability - Qiang Qu; Ming Wen; Mingzhu Cheng; Anwei Zhu; Biao Kong; Yang Tian (International Journal of Electrochemistry)
A novel particle-on-alloy nanomaterial has been designed and successfully synthesized for oxygen reduction (ORR) with high activity and long-term stability, in which well-isolated Pt nanoparticles are supported by amorphous NiCo nanoalloys. The Pt-on-NiCo nanostructures are prepared through the artificial active collodion membrane by one-step method, and experimental data reveals that Pt is isolated and spreads onto the amorphous NiCo nanosupport, and not only Pt but also Ni and Co are metallic in the Pt-on-NiCo nanostructures. The optimized Pt53-on-NiCo nanostructures show higher activities in both the onset potential and kinetic current density toward the ORR relative to the commercial Pt reference catalysts because the Pt-on-NiCo catalyst could lower the OHad, which is considered to inhibit the ORR toward water. Meanwhile, Pt-on-NiCo nanostructures exhibit relatively long-term stability with only ~8% loss in electrochemical surface area (ECSA) for Pt.